Electrical apparatus and associated equipment for use in explosive atmospheres of gas or vapour other than mining applications. Methods of meeting the explosion hazard other than by the use of flameproof or intrinsically-safe electrical equipment Part 2, (30th April 1986) - British Standards Institution
No abstract available